Services – SERVICES 2020 : 16th World Congress, Held as Part of the Services Conference Federation, SCF 2020, Honolulu, HI, USA, September 18-20, 2020, Proceedings /: 16th World Congress, Held as Part of the Services Conference Federation, SCF 2020, Honolulu, HI, USA, September 18-20, 2020, Proceedings. (2020) - Unknown
No abstract available